Modulators of Protein Kinase C Affect SR-BI-Dependent HDL Lipid Uptake in Transfected HepG2 Cells - Brunet, Rachelle (Hindawi Publishing Corporation, 2011)
SR-BI is a cell surface HDL receptor that mediates selective uptake of the lipid cargo of HDL, an important process in hepatocytes, driving reverse cholesterol transport from cells in the artery wall. To facilitate examination of factors that modulate SR-BI activity in hepatocytes, we have generated fluorescent protein-tagged versions of SR-BI that allow for facile monitoring of SR-BI protein levels and distribution in transfected cells. We show that deletion of the C-terminal cytosolic tail does not affect the distribution of SR-BI in HepG2 cells, nor is the C-terminal cytosolic tail required for SR-BI-mediated uptake of HDL lipids. We also demonstrate that the phorbol ester, PMA, increased, while protein kinase C inhibitors reduced SR-BI-mediated HDL lipid uptake in HepG2 cells. These data suggest that protein kinase C may modulate selective uptake of HDL lipids including cholesterol in hepatocytes, thereby influencing hepatic HDL cholesterol clearance and reverse cholesterol transport.